Communication Pattern of Women Migrant Workers Family at Sliyeg District in Indramayu - West Java - Slamet Mulyana; Duddy Zein; Agus Setiaman (Ikatan Sarjana Komunikasi Indonesia, 2017)
The purpose of this study was to determine and analyze factors that affect communication families of migrant workers, the level of relations of parents and children in a migrant worker family communication, and communication styles of communication parents in families of migrant workers in the district of Indramayu district Sliyeg. The benefits and outcomes of this research is an article that would be presented as a study in the scientific journal, both the national level and international level, as well as teaching material in several courses ie Interpersonal Communication and Social Communication Development.The method used in this research is descriptive quantitative method, with research areas in the District Indramayu regency Sliyeg persuasive selection. The collection of data obtained through questionnaires, interviews and observations of respondents as many as 40 heads of families of migrant workers.The results showed that the characteristics of the heads of families of migrant workers, namely age, education level, occupation, income level, number of children and the number of dependents is the driving factor that causes him to allow his wife to become migrant workers. The physical environment and the social environment are important factors that affect patterns of interaction and communication patterns of families of migrant workers. Level relationships of parents and children in a migrant worker family communication going pretty well. Style of parent communication in communication families of migrant workers support their mutual communication between parents and children.